2014
DOI: 10.2174/1874325001408010466
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Trochanteric Fractures with the Gamma3 Nail - Methodology and Early Results of a Prospective Consecutive Monitored Clinical Case Series

Abstract: Objectives: There is only sparse data on clinical results and complications of the third-generation Gamma nailing system (Gamma3, Stryker). Therefore, we started a large multi-centre case series in 2008. The aim of this paper is to present the study design and early results of a single arm of a prospective, consecutive, monitored, post-market follow-up evaluation of Gamma3 nails. Methods: From September 2009 to January 2012, 154 consecutive patients with an average age of 80 ± 1.43 years (50-99 years) and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…Regarding the literature data about third generation Gamma Nail, Sim et al 25 found the average operation time was 85 min, while Kelly et al 18 found the average intraoperative fluoroscopy time was 116 s. Furthermore, Wu et al 26 , Unger et al 27 and Arirachakaran et al 28 found average operation times were 67 min, 56 min and 62 min, while average intraoperative fluoroscopy times were 52 s, 62 s and 109 s, thus all these intraoperative fluoroscopies were longer than 50 s.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the literature data about third generation Gamma Nail, Sim et al 25 found the average operation time was 85 min, while Kelly et al 18 found the average intraoperative fluoroscopy time was 116 s. Furthermore, Wu et al 26 , Unger et al 27 and Arirachakaran et al 28 found average operation times were 67 min, 56 min and 62 min, while average intraoperative fluoroscopy times were 52 s, 62 s and 109 s, thus all these intraoperative fluoroscopies were longer than 50 s.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, 12-month-mortality rate of G3N ranges from 15,4% to 23,2% [ 13 , 22 , 23 ]. We reported lower rates possibly explained by improved anesthetic techniques and faster rehabilitation schemes as determinants of reduced mortality [ 23 ]. The death of patients was unrelated to surgery, but could be explained by high comorbidity index of the patients (median ASA score 3).…”
Section: Discussionmentioning
confidence: 99%
“…This Module is the third generation of intramedullary long and short GNs fixation. The development of the successful trochanteric and long gamma intramedullary nails as well as the small stature versions followed precisely a step-by-step improvement based on the clinical experience and outcome [4] .…”
Section: Introductionmentioning
confidence: 99%